Long-Term Outcomes of the Coarctation of the Aorta Stent Trials. (27th May 2021) - Holzer, Ralf J.; Gauvreau, Kimberlee; McEnaney, Kerry; Watanabe, Hanano; Ringel, Richard
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Long-term outcome data of stent-implantation for coarctation of the aorta are limited. We report up to 5 years of postimplant follow-up in patients enrolled into the COAST (Coarctation of the Aorta Stent Trial) and the COAST II trial (Covered Cheatham-Platinum Stents for Prevention or Treatment of Aortic Wall Injury Associated With Coarctation of the Aorta), evaluating the bare and Covered Cheatham-Platinum Stents for the treatment of coarctation of the aorta and associated aortic wall injury. Methods: Data was prospectively collected during the 2 multi-center studies, enrolling 248 patients (COAST: n=121, COAST II: n=127). Late follow-up data (48–60 month) was compared with immediate (1 month) and early (12 months) follow-up. Results: There was a notable decrease in the use of antihypertensive medication, from 53% at immediate, to 42% at early, and 29% at late follow-up. The cumulative incidence of stent fractures was 0% immediately, 2.9% at early, and 24.4% at late follow-up. Independent predictors for stent fractures at late follow-up were age <18 years, male sex, minimum stent diameter ≥12 mm, and use of bare metal stent. The cumulative incidence of reintervention was 1.6% at immediate, 5.1% at early, and 21.3% at late follow-up. Independent predictors for reinterventions at late follow-up were age <18 years, post implantation systolic arm-leg blood pressure gradient ≥10 mm Hg, minimum stent diameter at implantation <12 mm, and initial coarctation minimum diameter <6 mm. There were 13 patients with aortic aneurysms, with a cumulative incidence of 6.3% at late follow-up. Conclusions: Coarctation stenting is effective at maintaining obstruction relief up to 60 months postimplant with reduction in the number of patients requiring antihypertensive medication. However, an increase in-stent fractures and reinterventions were observed between medium and long-term follow-up. Covered stents appear to confer some protection from the development of stent fractures but do not provide complete protection from late aneurysm formation. Registration: URL: https://www.clinicaltrials.gov ; Unique identifiers: NCT00552812 and NCT01278303.